Pengaruh Harga, Keamanan dan Promosi Terhadap Keputusan Pembelian Toko Online Lazada - Kevin Prilano; Andriasan Sudarso; Fajrillah Fajrillah (Journal of Business and Economics Research (JBE), 2020)
The purpose of this study was to analyze the effect of price on Lazada online store purchase decisions, analyze the effect of security on Lazada online store purchase decisions, analyze the effect of promotions on Lazada online store purchase decisions, and analyze the effect of price, security, and promotion on online store purchase decisions Lazada This research method is a type of quantitative research. Data sources of this study include primary data and secondary data. The population in this study was the Environmental Society 19 in Tanjung Mulia Subdistrict, Medan Deli District, totaling 950 people. The sampling technique used in this study was purposive sampling and obtained as many as 125 customers. The data analysis technique used is the classic assumption test which includes normality test, multicollinearity test, and heteroscedasticity test, multiple linear regression, hypothesis testing which includes t test and F test, and coefficient of determination (r2). The results obtained from the t test results obtained t-value of the variable price of -2.668 smaller than the value of t table -1.658, t-value of security variable 13.490 is greater than the value of t table 1.658, and the t-value of the promotion variable 3.428 is greater than the value of t table 1.658. From the F test results obtained Fcount value of 94.732 is greater than the value of Ftable 2.68. From the test results the coefficient of determination obtained by 69.4% of the purchase decision variable is influenced by the price, security and promotion variables, while the remaining 30.6% is explained by the influence of other factors or variables outside the model such as brand image, distribution channels, service quality , and others that are not discussed in this study.